Is the performance of the dollar a random process? - Rolf Schneider (Intereconomics, 1989)
It is still frequently argued that a random process would be the best way of predicting the DM/dollar exchange rate. In the following empirical analysis, however, Dr. Rolf Schneider comes to the conclusion that the behaviour of the dollar can be explained largely in terms of basic economic variables.
Keywords: 330; Exchange Rates